The Impact of Negative Word of Mouth on Customers' Responses - Fariborz Rahimnia (مطالعات مدیریت راهبردی, 2014)
This study is to investigate the effect of negative word of mouth on customers' reactions considering the moderation role of tie strength. Accordingly, a scenario-based questionnaire was online distributed to 268 users of cell-phone operators. It should be noted that, face and content validity of the questionnaire were confirmed through the experts' opinions, and its reliability was calculated using the Cronbach's alpha. Research results indicated that the current customers are more engaged in exit and voice intention than loyalty intention in reaction to abandonment of unprofitable customers. Furthermore, reactions to abandonment of unprofitable customers are affected by tie strength between the current and abandoned customers. It can be concluded that, although the customer relationship management is considered as maintaining the relationship with profitable customers in most of the modern companies, marketing managers should make some appropriate strategies in order to control the unprofitable customers.